Comparative Foraging Behavior of Apis Cerana F. and Apis Mellifera L. in Rapeseed under Cage Condition in Chitwan, Nepal - Pudasaini, Rameshwor; Thapa, Resham Bahadur (International Journal of Applied Sciences and Biotechnology, 2014)
An experiment was conducted to determine the foraging behavior of Apis mellifera L. and Apis cerana F. in rapeseed under cage condition in Chitwan, Nepal during 2012-2013. This experiment showed that Apis cerana F. foraged extra 42 minute per day as compared to Apis mellifera L. Apis cerana F. were more attracted to nectar, whereas Apis mellifera L. were more attracted to pollen collection throughout the day. The activities, in into hives and out from hives, for both species were recorded more at 2:00 pm and least at 8:00 am. The highest in-out were observed at 2:00 pm on both species as Apis mellifera L. 44.33 bees entered into hives and 49.66 bees went out of hives, whereas lower number of Apis cerana F. 43.66 bees entered into hives and 48.16 bees were out of hives. Apis mellifera L. collect 1.22:1 and 0.41:1 pollen nectar ratio at 10:00 am and 4:00 am whereas at same hours Apis cerana collect 1.16:1 and 0.30:1 pollen nectar ratio. Apis cerana F. foraged significantly higher number of rapeseed flowers and plants as compared to Apis mellifera L. under caged condition. It shows that Apis cerana F. was more efficient pollinator as compared to Apis mellifera L. under caged condition. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11238 Int J Appl Sci Biotechnol, Vol. 2(4): 483-487